Kelios mintys dėl latvių senųjų raštų vienaskaitos kilmininko su -as ir daugiskaitos kilmininko su -us - Rosinas, Albertas (Baltistica, 2001)
SOME REMARKS ON THE GENITIVE SINGULAR IN -as AND THE GENITIVE PLURAL IN -us OF LATVIAN OLD MANUSCRIPTS In the translation of Catechismvs Catholicorum, as well as in Elger’s texts, the genitive singular in -es[-as] of (i̯)o-stem nouns results from the expanded sphere of application of the (rīt)-as- type, genitive in the Riga dialect; the latter choice must have been determined by the substantival genitive model of the strong declension in the native German language, which was structurally similar to the genitive model with limited application in the Latvian language. The form of the German article chosen by the translators – not the masculine genitive form tā, but the feminine form tās – appeared due to erroneously understood concord and the structural similarity of the form tās to the form of the masculine genitive singular of the article in the native language, cf. des. The nominal ‘genitive’ plural in -us (also spelt -es [–us]) is not a consequence of ‘assimilation’ to the demonstrative pronominal ‘genitive’ plural tuos, as is maintained by Endzelīns, because it is impossible to prove that the Western Latvian dialects (the Riga dialect included) could ever have possessed a ‘genitive’ of such a type. The ending in question in the old texts is rather typical of the masculine (i̯)o- and ii̯o-stem nouns only, except for some nouns whose gender may vary. Given that the idea of ‘assimilation’ is correct, in the old texts there should have appeared a similar type of ‘genitives’ in nouns of other stems, too, e.g. °pušus, °acus, °ļaužus, ‘debesus. The textual data allow one to assume that both the pronominal tuos-type form and the nominal genitive (vis)-us, (grēk)-us-type forms are just accusative plural forms which, due to the neutralization of the contrast between the genitive plural and the accusative plural in certain positions, are used alongside the genitive plural forms. The neutralization could have occurred first in prepositional constructions used by the Latvian-speaking German sociolect. For example, according to the model of proportional analogy no+gen. sg. : no+acc. sg. = no+gen. pl. : x, there appeared the construction no+acc. The second position of the neutralization in question could have evolved in the process of full nominalization when the governing of the accusative of transitive verbs was generalized so that it could apply to verbal abstracts and names of agents, too: atzīt / neatzīt tuos grēkus —> tuos grēkus (ne)atzīšana; salīdzināt tuos cilvēkus —> tuos cilvēkus salīdzinātajs, etc.